Fabrication Of Solar Fabric Using Titanium Dioxide Nanowires Based On Dye Sensitized Solar Cell Technique - Amat, Noor Faridah (2018)
Solar fabric is the third generation of photovoltaic device that converting solar energy to electrical energy to produce electricity.In order to reduce the cost manufacturing of solar cell,solar fabric is introduced as a cheaper manufacturing cost to generate solar energy.In this research work,it presents a comprehensive review on the synthesis,structure characterization,the performance of nanostructures in term of conductivity and lastly, fabrication process to create the solar fabric.Titanium dioxide (TiO2) has been used to develop nanowires as the characteristics are better than other semiconductor material.The nanowires are succeeding to develop via hydrothermal method to fabricate solar fabric that applying dye sensitized solar cell (DSSC) technique. Generally,there are various techniques to develop the nanowires.But this research work,hydrothermal method,sol-gel method and electrospinning technique were conducted in the laboratory.By comparing the result of the three methods,only sol-gel method unsuccessfully to develop nanowires.Even though electrospinning is succeeding to produce nanowires,but,the quantity is smaller,the process takes a long time and use high voltage.The characteristic of the nanowires is measured by analyzing using FESEM, XRD,BET,UV-Vis and conductivity testing to figure out the quality or the best nanowires.The best 4 samples has been figured out and it was used to fabricate the solar fabric.The solar fabric has applied DSSC technique.The best 4 sample which are A,B,C and D were used to fabricate the solar fabric and the efficiency of each device have been measured using a solar simulator and potentiostat.The devices have been further investigated using electrochemical impedance spectroscopy (EIS) to measure the interaction of internal resistance in the devices.From the results,sample D becomes the best TiO2 nanowires compared to the rest of the samples,which has achieved a high performance at 1.46%.On the other hand, sample B showed low efficiency at around 0.08%,while sample A displayed about 0.4%,and sample C exhibited 1.2%.